Analisis Penyebab Kerusakan Head Truck-B44 Menggunakan Metode FMEA dan FTA (Studi Kasus : PT. Bima, Site Pelabuhan Berlian) - Bimby Khrisdamara; Deny Andesta (Fakultas Teknik, 2022)
A company if wants to survive in the face of the era of globalization is required to improve the quality of service continuously. PT. BIMA is a company engaged in maintenance and port equipment providers. In the service process, PT. Bima has 5 types of transport aircraft, but the most number of units and often used to operate is the head truck. Based on the history data, there are B44 head truck units, often damage problems in several parts, namely damage to Accu, Tire, Coupling, Hose Spiral and Separator components. The purpose to identify the type of damage that occurred, conduct an assessment which is then continued analysis of the FTA method to find out the factors that cause damage and provide recommendations. The results showed that with fmea analysis it was found the type of damage that had the largest RPN value score was the type of damage to the head truck-B44 unit in the accu section which had a RPN value of 181. While the results of the FTA analysis found that the cause of damage to the accu drop was the use of overtime units, damaged accu clamps, pull accu and preventive maintenance intervals were less accurate.